Modalitas Politik Incumbent di Pilkades (Studi terhadap Kemenangan Aminanto di Pilkades Sidoharjo-Bangka Selatan) - Ibrahim Ibrahim; Bahjatul Murtasidin; Purnomo Arbi (Ideas Publishing, 2023)
This study aimed to find out what Aminanto political modalities had and how Aminanto s efforts in gaining power in Sidoharjo village. The research method used was a qualitative method with a descriptive approach. The findings of this study indicated that Aminanto s social capital came from three forms such as popularity, social networks, and social relationships. Meanwhile, his cultural capital came from the similarity of customs and culture he had with the people of Sidoharjo. Finally, economic capital that came from personal funds or no help from any party. The efforts made by Aminanto were the utilization forms of political modality he had.